2011
DOI: 10.1105/tpc.111.085415
|View full text |Cite
|
Sign up to set email alerts
|

Keep an Eye on PPi: The Vacuolar-Type H+-Pyrophosphatase Regulates Postgerminative Development inArabidopsis     

Abstract: Postgerminative growth of seed plants requires specialized metabolism, such as gluconeogenesis, to support heterotrophic growth of seedlings until the functional photosynthetic apparatus is established. Here, we show that the Arabidopsis thaliana fugu5 mutant, which we show to be defective in AVP1 (vacuolar H + -pyrophosphatase), failed to support heterotrophic growth after germination. We found that exogenous supplementation of Suc or the specific removal of the cytosolic pyrophosphate (PPi) by the heterologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
316
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(328 citation statements)
references
References 63 publications
12
316
0
Order By: Relevance
“…Previously, it was reported that the null mutants fugu5-1, fugu5-2, and fugu5-3 have an increased PPi concentration in the cytosol. This increased concentration has a visibly negative impact on the development of cotyledons and hypocotyl elongation in etiolated seedlings, due to metabolic inhibition of key enzymes by PPi overload (Ferjani et al, 2011). We compared the cotyledon growth of the triple KO mutant to the three fugu5 alleles but did not observe the typical elongated shape of cotyledons in AVP1 mutants (Fig.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, it was reported that the null mutants fugu5-1, fugu5-2, and fugu5-3 have an increased PPi concentration in the cytosol. This increased concentration has a visibly negative impact on the development of cotyledons and hypocotyl elongation in etiolated seedlings, due to metabolic inhibition of key enzymes by PPi overload (Ferjani et al, 2011). We compared the cotyledon growth of the triple KO mutant to the three fugu5 alleles but did not observe the typical elongated shape of cotyledons in AVP1 mutants (Fig.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedmentioning
confidence: 99%
“…7A). As previously described, the fugu5-1 line complemented with the yeast IPP1 soluble pyrophosphatase developed normal cotyledons (Ferjani et al, 2011). In addition, we combined the ppspase1-1 and pecp1-1 mutations with the fugu5-1 allele to determine whether combining the three mutations could enhance the elongated cotyledon phenotype or lead to a new phenotype (Fig.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedmentioning
confidence: 99%
See 3 more Smart Citations